Implementation of Islamic religious education learning based on the JSIT curriculum - Aula Nafilah; Ahmad Muflihin (Himpunan Pengembang Kurikulum Indonesia, 2025)
Islamic Religious Education plays a vital role in shaping students' character to become faithful and morally upright individuals. The JSIT curriculum emerges as an integrative solution that unites general and religious subjects while emphasizing the balanced development of cognitive, affective, and psychomotor domains. This study aims to examine the planning, implementation, and evaluation processes of Islamic Religious Education learning based on the Jaringan Sekolah Islam Terpadu (JSIT) curriculum in Grade I at SDIT Harapan Bunda, Semarang City. This research employs a qualitative approach, utilizing field study methods, and data were collected through observation, interviews, and documentation. The research subjects consist of teachers and Grade I students at SDIT Harapan Bunda Semarang. The findings show that 1) the planning process is carried out systematically by formulating learning outcomes, setting learning objectives, developing textbooks, preparing lesson plans, and designing learning assessments; 2) the implementation runs effectively through three main stages opening, core activities, and closing; and 3) the evaluation is conducted using various instruments, integrated assessments covering cognitive, affective, and psychomotor aspects, and reporting of student outcomes through two types of report cards: the official government report and the JSIT specific report card. Abstrak Pendidikan Agama Islam berperan penting dalam membentuk karakter peserta didik yang beriman dan berakhlak mulia. Kurikulum JSIT hadir sebagai solusi integratif yang menyatukan pelajaran umum dan agama, serta menekankan pengembangan aspek kognitif, afektif, dan psikomotorik secara seimbang. Penelitian ini bertujuan untuk mengetahui proses perencanaan, pelaksanaan, dan evaluasi pembelajaran Pendidikan Agama Islam berbasis kurikulum Jaringan Sekolah Islam Terpadu (JSIT) pada kelas 1 di SDIT Harapan Bunda kota Semarang. Metode yang digunakan adalah kualitatif dengan penelitian lapangan serta menggunakan teknik pengumpulan data berupa observasi, wawancara, dan dokumentasi. Subjek penelitian ini adalah guru PAI dan peserta didik kelas I SDIT Harapan Bunda kota Semarang. Hasil dari penelitian ini menunjukkan bahwa 1) Perencanaan pembelajaran dilaksanakan secara sistematis dengan menyusun capaian pembelajaran (CP), menentukan tujuan pembelajaran, menyusun buku teks pelajaran, menyusun RPP, dan menyusun asesmen pembelajaran; 2) Proses pelaksanaan pembelajaran berjalan efektif dengan melalui tiga kegiatan pembelajaran yakni kegiatan pembuka, inti, dan penutup; dan 3) Evaluasi dilakukan melalui instrumen evaluasi, penilaian terpadu yang meliputi aspek kognitif, afektif, dan psikomotorik serta pelaporan hasil belajar peserta didik dengan dua jenis raport yakni raport dinas dan raport khas JSIT. Kata Kunci: implementasi kurikulum; kurikulum JSIT; pendidikan agama Islam